Relationship between neonatal gastroschisis and maternal body mass index in a United Kingdom population. (March 2017) - Hale, Joann; Derbyshire, Abigail; Taylor, Alexander; Osmond, Clive; Wellesley, Diana; Howe, David T.
Abstract: Objective: It has been reported that gastroschisis is associated with low maternal body mass index (BMI). We tested this hypothesis in the UK. Study design: We studied cases of gastroschisis ascertained from the regional fetal congenital anomaly register. We compared each affected mother with two controls from the birth register and maternity database. The first control was the next mother to deliver in the hospital, representing the normal population of mothers. The second control was the next mother to deliver an unaffected child whose age was within one year of that of the index case controlling for maternal age. Results: There was a strong inverse association between maternal age and gastroschisis. An inverse association between gastroschisis and birth order was eliminated by adjustment for maternal age. The average age of mothers of affected children was 22.1 years; of the next delivery control was 28.8 years, and of the age matched control was 22.2 years. A weak non-statistically significant negative association between BMI and gastroschisis was further weakened by adjustment for maternal age. Conclusion: Our results confirm the previously reported association between low maternal age and gastroschisis but suggest that within our UK population the link between low BMI and gastroschisis reported elsewhere is explained by younger mothers being thinner.